1996
DOI: 10.1021/bi960835f
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Helicity and Membrane Surface Charge Modulate the Balance of Electrostatic and Hydrophobic Interactions with Lipid Bilayers and Biological Membranes

Abstract: An amphipathic model peptide, KLALKLALKALKAAKLA-NH2, and its complete double D-amino acid replacement set was used to analyze the process of peptide binding at lipid vesicles of different surface charge and to determine the structure of the lipid-bound peptides using CD spectroscopy. The relationship between peptide helicity, model membrane permeability, and biological activity has been studied by dye release from liposomes and investigation of antibacterial and hemolytic activity. The accumulation of cationic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
307
1
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 384 publications
(343 citation statements)
references
References 41 publications
32
307
1
3
Order By: Relevance
“…It is not unexpected that the antibacterial activities of peptides vary with their chain lengths (9,10,11,31,51). One previous study has reported that antibacterial activity decreases with an increase in the chain length of the peptides, while the reverse situation was found for hemolytic activity (31).…”
Section: Discussionmentioning
confidence: 97%
“…It is not unexpected that the antibacterial activities of peptides vary with their chain lengths (9,10,11,31,51). One previous study has reported that antibacterial activity decreases with an increase in the chain length of the peptides, while the reverse situation was found for hemolytic activity (31).…”
Section: Discussionmentioning
confidence: 97%
“…11 Pilot experiments have shown that both human and sheep erythrocytes respond similarly in this hemolytic assay (data not shown). In brief, the erythrocytes were washed and resuspended in Tris-buffered saline.…”
Section: Hemolytic Activitymentioning
confidence: 91%
“…Multiple studies demonstrated that peptide helicity might be more important for toxicity (neutral membrane) than antimicrobial activity (negatively charged membrane) of AMPs (Pouny et al, 1992;Dathe et al, 1996). The most convincing evidences are from D-amino acid substitution on model peptides.…”
Section: Helicitymentioning
confidence: 99%